3D flow measurements in regular breaking waves past a fixed submerged bar on an impermeable plane slope. (3rd August 2016) - Clavero, M.; Longo, S.; Chiapponi, L.; Losada, M. A.
Abstract : The velocity fields induced by regular breaking waves past a fixed bar on a 1 : 10 rigid plane slope were measured and analysed using a volumetric particle-tracking velocimetry system. Under specific conditions, the interaction between waves and morphological features steepens the waves, which eventually break. The geometry of the boundaries of the present experiments is common in natural environments, where reefs, sand and gravel bars, and submerged coastal structures, interact with the incoming wave field, 'affecting' the transport budget of substances (sediment, nutrients and pollutants), with relevant consequences on the water quality. The aims of the present work are the analysis of the flow field in the breaker, and the quantification of the terms in the equations usually adopted for modelling the flow and the turbulence. Two sets of attacking monochromatic wave trains with different periods and heights were used to generate a data set of instantaneous velocity, which was further analysed to extract turbulence. The measurement volume extended from the wave crest to a portion of the domain below the wave trough. The balance of linear momentum for the average field and the balance of turbulence were scrutinized, and included all the terms in a three-dimensional (3D) approach. The analysed data and results are original and novel because they include all the contributions derived from the 3D structure of a real flow field, and constitute a huge data set for the calibration of numerical codes.